The Adverse Effects of the European Dealings with Immigrants on the Mediterranean Countries: Libya as A Case Study (2012-2022) - صالح السطي الفيتوري (Dirasat in Economics and Business, 2024)
With the emergence of mankind and the increase in its numbers, migration and travelling appeared in the parts of the earth, and people moved from one place to another for several reasons, including: seeking livelihood, a better life, and security. And with the increase in the number of societies and their transformation from simple societies to political entities, which was accompanied by the establishment of modern states and the resulting political divisions of states, these political entities began to preserve their societies within their specific political scope. Due to the increase in population and overcrowding in some places, with limited resources, the members of those communities began to search for more resources and a better life. They were rejected by the political entities that plan according to the available resources they have in order to meet the needs of their communities within the limits of their political scope - the state. There were many circumstances that contributed to the phenomenon of migration, including: natural, represented by drought, lack of rain, desert encroachment, and lack of resources, as well as political circumstances, such as: wars, conflicts, poverty, and dictatorial regimes. And given that the northern shore of the Mediterranean is full of privileges, in addition to the tremendous scientific progress, the industrial revolution, and the concentration of wealth in it. As for the opposite side in the southern Mediterranean, many migrations occurred from the south to the north because they need each other. However, each society has its own accounts, so the old continent suppressed immigrants with all force, and it reached the point of interfering in the affairs of the source and transit countries, destabilizing their security and stability, and violating their sovereignty in order to achieve its goal. It supported unofficial groups, with or without the knowledge of the official institutions in the concerned countries, which formed groups parallel to the official institutions and now possessed strength and capabilities that exceeded those possessed by the official security institutions. This contributed to political instability, and exacerbated the conflict within the supported power in order to obtain more control, influence, and money, all with the blessing of a regional power and international organizations.